Comparative assessment of drought indices for evaluating drought patterns in Peninsular Malaysia - Ng J.L.; Huang Y.F.; Chong A.H.; Lee J.C.; Abdulkareem M.; Noh N.I.F.M.; Mirzaei M.; Ahmed A.N. (IWA Publishing, 2024)
Drought has been the main environmental issue in Peninsular Malaysia. Hence, this study undertook a thorough evaluation of drought assessment methodologies and focused on the temporal analysis of multiple drought indices, namely, the standardised precipitation index (SPI), deciles index (DI), percent of normal precipitation index (PNPI), rainfall anomaly index (RAI) and Z-score index (ZSI) across timescales of one-, six-and 12-month durations. This assessment incorporates the average moving range (AMR), MannKendall (MK) test and Sens slope estimator in temporal analysis and the results showed that shorter timescales lead to higher fluctuation in AMR values, indicating short-term droughts are best assessed using drought indices of shorter timescale. It was found that most drought indices exhibited a similar trend and trend magnitude in all timescales. SPI is utilised as the standard model for the accuracy evaluation of drought indices using root mean square error (RMSE), mean absolute error (MAE) and mean absolute percentage error (MAPE). The results showed that ZSI has the highest accuracy of all indices. The novelty of this study lies in evaluating the accuracy and temporal characteristics of precipitation-based drought indices in tropical areas, particularly in Peninsular Malaysia. 2023 The Authors.